1999
DOI: 10.1021/ac9905470
|View full text |Cite
|
Sign up to set email alerts
|

Superheated Heavy Water as the Eluent for HPLC-NMR and HPLC-NMR-MS of Model Drugs

Abstract: Superheated heavy water can be used as the eluent for reversed-phase chromatography with on-line HPLC-NMR and HPLC-NMR-MS detection. The method has been demonstrated for the separation of model drugs (analgesics and caffeine) on a poly(styrene-divinylbenzene) stationary phase in isothermal and temperature-programmed modes. One-and two-dimensional spectra could be obtained with less interference from the mobile phase than with conventional HPLC-NMR eluents. Unlike supercritical fluid chromatography-NMR, the spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 71 publications
(36 citation statements)
references
References 20 publications
1
35
0
Order By: Relevance
“…Smith et al [43] used these phases for the separation of model drugs employing superheated heavy water. They also used a phosphate buffer at a pH of 3 for the elution of salicylamide and encountered no problems with the stability of the stationary phase.…”
Section: Plrp-smentioning
confidence: 99%
“…Smith et al [43] used these phases for the separation of model drugs employing superheated heavy water. They also used a phosphate buffer at a pH of 3 for the elution of salicylamide and encountered no problems with the stability of the stationary phase.…”
Section: Plrp-smentioning
confidence: 99%
“…For example as well as being compatible with ultraviolet spectroscopy and fluorescence detection, where water has virtually no background absorbance down to 190 nm, it can also be used with refractive index and electrochemical detection. There is no reason why it should not be compatible with evaporative light scattering detection and it has been coupled to mass spectroscopy [16].…”
Section: So How Does Superheated Water Overcome These Problems?mentioning
confidence: 99%
“…Interfacing is a problem but can be overcome. Figure 2 The absence of organic hydrogens in the eluent also means that if deuterium oxide is used as the eluent, on-line proton nuclear magnetic resonance spectroscopy (LC-NMR) give a background free signal [19]. This is much cheaper than using deuterated methanol or acetonitrile in the eluent.…”
Section: So How Does Superheated Water Overcome These Problems?mentioning
confidence: 99%
“…Previous studies have demonstrated the applicability of high temperature separations to a range of pharmaceuticals [9], with examples such as analgesics [10], vitamins [11] and thalidomide [12] and compounds of environmental interest, such as the triazine herbicides [13]. However, as a method it has been constrained by the poor thermal stability of conventional octadecyl bonded silica based phases but this problem can be overcome by using polymeric materials, such as polystyrene divinylbenzene or alternative thermally stable phases, such as coated zirconia [14] or porous graphitic carbon [13].…”
Section: Introductionmentioning
confidence: 99%